Fate and moral responsibility in stoicism - Yırcalı, Gökçe. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
The Stoics have an intricate account of fate which is interconnected with many branches of their thought, their ontology, logic, physics, theology and ethics. It is the Stoic claim that agents could be held to be morally responsible in a deterministic world. This thesis aims to show that the arguments put forward by Chrysippus concerning the compatibility of fate and moral responsibility are not completely successful; on the other hand, it is through the Stoic conception of reason that fate and moral responsibility could be made compatible in Stoicism. Accordingly, in the first part the concept of fate is explained, in the second part the Chrysippean arguments are analyzed, and in the final part the functions of reason are laid out.
Keywords: Stoics.